Is difficult item relevant to higher cognitive process level?: Proof from the geomorphology topic assessment based on Bloom’s and Marzano cognitive taxonomy - Listyo Yudha Irawan; Siti Nur Farihah; Agus Dwi Febrianto; Aulia Amatullah; Nurul Ratnawati; Bayu Kurniawan (Psychology, Evaluation, and Technology in Educational Research, 2026)
Assessment of learning outcomes needs to consider the appropriateness between the level of difficulty of questions and the cognitive level being measured, especially in Physical Geography–Geomorphology material that requires higher-order thinking skills (HOTS). This study aims to analyze the relationship between the level of difficulty of questions and cognitive levels as defined by Bloom's Taxonomy and Marzano's Taxonomy. The study employs a quantitative descriptive approach by developing ten essay-type questions classified according to both taxonomies. The difficulty level analysis was conducted using Classical Test Theory (CTT) with the parameter of the proportion of participants who answered correctly. The research results indicate that difficulty levels do not always correlate with cognitive levels. In Bloom's Taxonomy, C1 questions tend to be the easiest, while in Marzano's Taxonomy, C3 questions are actually easier than other levels. This demonstrates that difficulty levels and cognitive levels are two distinct concepts, so the perception that HOTS questions are always difficult is not entirely accurate. In conclusion, the development of assessment instruments must consider the relationship between learning objectives, cognitive levels, and item characteristics. The study recommends integrating HOTS-based learning into geomorphology material through the use of contextual media and geospatial technology to support meaningful assessment and the development of 21st-century skills.